Politik Identitas Masyarakat Jawa Pasaman Barat dalam Pilkada di Kabupaten Pasaman Barat - Riyadi, Akbar; Arifin, Zainal; Zetra, Aidinil (Forum Ilmu Sosial, 2018)
This study discusses about Javanese ethnicity having one of the potential votes in the elections even though as a minority group. This phenomenon occurs in West Pasaman Regency. Javanese ethnic involvement in the pilkada was based on the instruction of the community leaders to elect the Javanese candidates who had advanced in the elections. On the other hand, potential Javanese ethnic groups ask for support from the community to give voting rights. This study aims to analyze Javanese ethnic identity politics in the West Pasaman regency election. This research uses qualitative method with phenomenology type. Research informants are selected using purposive sampling technique to obtain the required data. The informants interviewed the leaders of the Javanese communities, Minang and Mandailing figures, scientists who understood the community, candidates who advanced in the elections, the success team and the chairman of the West Pasaman Regency DPRD. The results of this study found First Identity similarity was obtained through a long process of adaptation, as well as through the background of individuals/groups from transmigration, retired military officers and from Suriname. Both similarities in race, religion, national origin, or a combination of these categories created an inter-ethnic Javanese ethnicity in a community shelter. The three Javanese ethnics as having the potential for votes are based on joint solidarity to choose their own ethnicity in the elections, the aim of the struggles to place their representatives in the government and provide benefits for their existence. The fourth Political identity is carried out by Javanese as the vice regent candidate, namely the campaign by asking for support to the Javanese community and conducting political contracts.